A cryptographic processor for arbitrary elliptic curves over GF(2m). (6th January 2009) - Eberle, Hans; Gura, Nils; Shantz, Sheueling Chang; Gupta, Vipul
We describe a cryptographic processor for Elliptic Curve Cryptography (ECC). The processor performs point multiplication for elliptic curves over binary polynomial fields GF(2m) up to a field degree of 255. In contrast to other designs that only support one curve at a time, our processor is capable of handling arbitrary curves. We have implemented the cryptographic processor in a Field-Programmable Gate Array (FPGA) running at a clock frequency of 66.4 MHz. Its performance is 6955 point multiplications per second for named curves over GF(2163) and 3308 point multiplications per second for generic curves over GF(2163).